ANALISIS FAKTOR KEBERMINATAN UNTUK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA ALUMNI SMAN 1 SAMBAS - Rahayu, Sri; Salim, Izhar; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ The title of this thesis is "Analysis of Factor of Interest to Continue Education To Higher Education At Alumni SMA Negeri 1 Sambas". The purpose of this research is to know the interest of the alumni of SMA Negeri 1 Sambas to continue to university in view of several factors: The Factor Inner Urge, The Factor of Social Motive, Emotional Factor at SMA Negeri 1 Sambas alumni. The approach used in this research is qualitative approach with description method. Techniques used in data collection are observation, interview and documentation with data collection tool interview guides, field notes and documentation. Informants in this study are seven alumni of SMA Negeri 1 Sambas graduated in 2016 who continue to public and private universities in Sambas, Pontianak and Java island. The results of this study indicate that the interest of alumni is seen from 1) The Factor Inner Urge, a strong desire for a thing to be achieved so that the result is good, for example go to college in accordance with the majors of interest, 2) The Factor Of Social Motive, when parents provide support and because of the scholarships and invitation path without a test for admission to college, 3) Emotional Factor, the high kesemangatan from within Alumni SMA Negeri 1 Sambas to continue to college for example college while working.Keywords: The Factor Inner Urge, The Factor Of Social Motive, Emosional Factor